Unwriting Maya Literature : Ts'íib as Recorded Knowledge - Worley, Paul M., 1976-; Palacios, Rita M. (Book collections on Project MUSE., 2019)
"This volume provides a decolonial framework for reading Maya and Indigenous texts"--Provided by publisher